2010 IEEE Conference on Robotics, Automation and Mechatronics 2010
DOI: 10.1109/ramech.2010.5513194
|View full text |Cite
|
Sign up to set email alerts
|

Posture stabilization of Skid Steer Wheeled Mobile Robots

Abstract: This paper represents the posture stabilization of a Skid Steer Wheeled Mobile Robot (SSWMR). Although, in mobile robots lateral skidding of the wheels occurs when turning at high speed, wheels of a SSWMR laterally skid in every rotational maneuver even for low speeds yielded the non-skidding nonholonomic constraint to be violated. In order to compensate the effects of parameter uncertainties, an adaptive torque controller is developed based on tunable dynamic oscillator. The Globally Uniformly Ultimately Boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…They have used the tunable dynamic oscillator to get globally uniformly bounded stability of the proposed control algorithm. The same idea can be found in [6] and [7].…”
Section: Introductionmentioning
confidence: 76%
“…They have used the tunable dynamic oscillator to get globally uniformly bounded stability of the proposed control algorithm. The same idea can be found in [6] and [7].…”
Section: Introductionmentioning
confidence: 76%
“…They have used tunable dynamic oscillator to get globally uniformly bounded stability of proposed control algorithm. The same idea can be found in [12] and [7].…”
Section: Introductionmentioning
confidence: 76%
“…Authors have shown that skidsteering mobile platform is an underactuated system on dynamic level with non-stationary velocity constraint (nonstationary kinematics). The same idea can be found in [14] and [9]. This paper focuses on the second possible approach to solve the under-actuation problem -it is extended factitious force method where the first announcement about this method, for single factitious force, can be found in [11].…”
Section: Underactuated Dynamicsmentioning
confidence: 99%